A microbiological study of non-gonococcal proctitis in passive male homosexuals. Issue 673 (November 1981) - Munday, P. E.; Johnson, A. P.; Thomas, B. J.; Jeffries, D. J.; Dawson, S. G.; Osborn, M. J.; Philip, S.; Harris, J. R. W.; Taylor-Robinson, D.
Abstract : In a study of 180 male homosexual patients attending a venereal disease clinic, a correlation was sought between symptoms and signs of proctitis and the isolation of Neisseria gonorrhoeae, group B streptococci, Chlamydia trachomatis, Ureaplasma urealyticum, Mycoplasma hominis and herpes simplex virus. Faecal specimens were examined for enteric pathogens and serological tests for hepatitis B virus, syphilitic and chlamydial infections were performed. There was no association between proctitis, as diagnosed by examination of a Gram-stained rectal smear, and the isolation of any micro-organism or detection of a positive serological test. There was, in addition, no association between any symptom or abnormal physical sign and any positive microbiological findings. Since 23% of patients from whom N. gonorrhoeae was isolated had no abnormal physical signs, it is difficult to assign a pathogenic role to other micro-organisms isolated from patients with and without clinical signs of proctitis. Approaches to further investigation of the problem are discussed.